COSTOMARY USE OF ZONONG IN THE JAYAWIJAYA REGENCY : (A SOSIOLOGICAL APPROACH DANI TRIBE) - Irma Yeny (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2010)
Regional development in Papua especially in Jayawijaya district often face land conflictt. The same understanding correspond to its area could minimize land conflict and maximize positive impact to support the next area development. This research aims to describe cultural aspects in land utilization of Dani tribe, Jayawijaya district. These aspects are important to be taken in to consideration when developing its area and community. Data collection was done through descriptive survey method with 20 key respondents. Analysis was done through social planning analysis based on perfect condition approach (Soekamto, 1990). Results showed there were two indigenous territorial division known as okama (forest area) and Uma-selekma (residential areas and management). There are 4 (four) rules in the use of natural resources resources including 1) the rules of customary rights, 2) the rules of land use, 3) the rules of forest use and 4) therules of water use. Customary territorial division along ethnic / clans have managed the universal land use that impact on the creation of essential for peace the life and harmonious relationship between humans and the natural environment. The indirect relationship of social structure and economic structure of Dani tribe has established a system of norms thatallow members of the community to cooperate in managing natural resources. Norm system in the existing agricultural activities remained at traditional level that seem to slow down the community development. These changes can be done through the ancient cultures with elements, such as : 1) technology tools, especially agricultural equipment and a modern house health concerned, 2) the economy improvement through the intensification of agricultural land (Agroforestry) and patterns of effective livestock, 3)implementing of healthy lifestyle and a house for one family only to reduce the dependance of living in one house. 4) Increasing the role of clean for good understanding of the Dani people in achieving bettrer life, especially in improving the welfare of the family. The strong belief to the clean chief would provide the real change in community through strong and agent of change leaderships.